Latihan Relaksasi Otot Progresif Pada Lansia Penderita Penyakit Degeneratif Di Kelurahan Tamalanrea Jaya Kota Makassar - Fajransi, Andi; Nurbaya, Sitti; Fauzia, Lisa; Sabil, Fitri A; Wijayaningsih, Kartika Sari (Universitas Negeri Gorontalo, 2025)
Degenerative disease is a health condition that is often experienced by the elderly which is characterized by a gradual decline in body function, this disease has various symptoms such as chronic pain, muscle stiffness and decreased mobility so that it is difficult to carry out daily activities. From the results of data collection in RW 01, Tamalanrea Jaya Village, it was found that 50 elderly people had degenerative diseases and complained of body aches, difficulty sleeping soundly and getting tired quickly. Therefore, community service activities were carried out in the form of progressive muscle relaxation training activities where this relaxation training involves relaxing and contracting certain muscles periodically which can help achieve optimal physical and mental conditions. This activity was attended by 30 participants who began with checking blood pressure and blood sugar then simulating progressive muscle relaxation training. Based on the evaluation results, participants felt more relaxed and comfortable. This activity is expected that participants will continue to do progressive muscle relaxation training at their respective homes so that they can improve their quality of life.